EVALUATION OF THE GENOTOXICITY OF ESSENTIAL OIL FROM ORIGANUM COMPACTUM BENTH. IN HUMAN LYMPHOCYTES - Sbayou, Houda; Talbi, Hayat; Talha, Ibtissam; Amghar, Souad; Hilali, Abderraouf (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Essential oils with antimicrobial and antioxidant activities have gained importance. This study was conducted to investigate the genotoxic potential of the essential oil of Origanum compactum. Methods: Micronucleus test and proliferation index (PI) were used to evaluate the genotoxic effect of the essential oil of O. compactum on human lymphocytes. Results: The results demonstrated that the PI values were influenced by the tested essential oil. An increase in concentration of essential oil also caused the appearance of micronuclei. Conclusion: The results of the present work suggest that O. compactum essential oil exhibited genotoxic activity at higher concentration. Further studies are necessary to confirm these findings. Keywords: Origanum compactum, Human lymphocytes, Proliferation index, Micronucleus test.